Teacher, Translator, Information and Communication Technologies at Escuela de Idiomas of Universidad de Antioquia: Realities and Challenges - Ardila Restrepo, María Elena; Becerra Naranjo, Luz María; Cañas Gil, Natalia Isabel (Íkala, Revista de Lenguaje y Cultura, 2012)
This qualitative, exploratory and descriptive study was based on class observations and interviews of students and teachers. This research led us to characterize the use of the Information and Communication Technologies (ICTs) in Education inside the language acquisition process, their role within curricular flexibility, and their underused potentialities in the context of study. We conclude that the use of the Internet favors the development of linguistic competence, and that we are witnessing a transition of teachers' practices and beliefs. However, there is still an urgent need for preparation, collaborative work and research on ICTs in education to promote a more enriching use of the resources. Besides, we propose an introduction of ICTs in education as a curricular innovation and not only as a technological one.